(untitled) (REMUNOM, 2024)
Abstract The world is currently experiencing a change in the age range of its population. The number of elderly people has been growing exponentially, linked to this factor, the number of illnesses directly related to age is also high. Parkinson’s is one of the diseases that frequently affects the elderly in Brazil and around the world. According to data from the Brazilian Institute of Geography and Statistics, life expectancy in 2017 is 76 years and with projections that by 2040 the elderly population will be approximately 17.41%. In PD, the main clinical manifestation is parkinsonian syndrome, resulting from impairment of the nigrostriatal dopaminergic pathway. PD is the most common cause of “parkinsonism”. This designation is phenomenological and syndromic, and can appear in different pathologies. Parkinsonism is characterized by: Resting Tremor, A rhythmic tremor that usually begins in one of the hands when at rest. Parkinsonism or parkinsonian syndrome is one of the most types of movement disorders and presents with 4 basic components: akinesia, weakness, tremor and postural instability. At least two of these components are necessary to characterize the syndrome. In the national literature researched, no articles were found that presented valid results of epidemiological studies of Parkinson’s disease. The data obtained was through the Brazilian Government’s epidemiological data portals, which record that in Brazil, there are no official estimates, but Brazil is going through a demographic transition with an aging population. This leads to the prevalence of common pathologies in old age. According to IBGE, the number of men and women over 60 years of age increased by 18% in the last five years and, in 2017, there were more than 30 million. PD has an unknown origin, however some studies indicate that it can be caused by a set of factors. Among them, you can mention the result of a combination of genetic predisposition with exposure to environmental toxic factors. Before starting treatment for Parkinson’s disease, you need to be sure of the diagnosis. Drug treatment cannot abolish all symptoms, and Physiotherapy is therefore recommended. Keywords: Parkinson’s disease; Neurodegenerative; Aging.